Improved Dielectric and Electrical Properties of PANI Achieved by Using Low Cost Mineral Additive - Kilic, Mehmet; Karabul, Yasar; Ozdemir, Zeynep Guven; Misirlioglu, Banu Sungu; Icelli, Orhan (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
In the present study, polyaniline (PANI) conducting polymer was mechanically doped with volcanic basalt rock (VBR), sodium metasilicate (Na2SiO3), and sodium tetraborate (borax) minerals at 10 to 50 wt%, to improve the dielectric response. The influence of these mineral additives on the complex dielectric, electrical modulus, and AC impedance spectra of the PANI was investigated. It was revealed that among the mineral additives, the highest.. is achieved for 50 wt % sodium metasilicate doped PANI composite. In addition, the appearance of peaks in the imaginary component of the electric modulus plots, for especially borax and sodium metasilicate doped samples, indicates the existence of a relaxation process. In addition, the Cole-Cole plots in the complex electrical modulus plane suggests a non-Debye type of relaxation. The single semi-circle arcs observed in Nyquist plots for PANI/Na2SiO3 composites indicates a dominant grain (bulk) contribution. Moreover, the bulk resistance and capacitance values for PANI/Na2SiO3 composites were found to be in the order of MO-GO and pF, respectively. While the AC conductivity spectrum of the PANI/VBR composites obeys the Nearly Constant Loss model, the PANI/Borax and PANI/Na2SiO3 composites were found to obey the Super Linear Power Law model. In conclusion, the low cost Na2SiO3 additive with different weight percentages for PANI shows remarkable effects on the dielectric and electrical properties.
Keywords: dielectric measurements; polyaniline; basalt; sodium metasilicate; borax; electrical modulus; AC CONDUCTIVITY; RELAXATION; IMPEDANCE; SPECTROSCOPY; BEHAVIOR; Engineering; Physics